The Effectiveness of Educative, Supportive, and Administrative Cycle (ESA-C) Clinical Supervision Model in Improving the Performance of Public Hospital Nurses - Setiawan, Asep; Anna Keliat, Budi; Rustina, Yeni; Prasetyo, Sabarinah (KnE Life Sciences, 2019)
Consistent supervision affects nurse performance, but in its implementation in nursing care in Indonesia, supervision tends to be more monitoring in nature and lacking the efforts of educating, motivating, training, and directing. The clinical supervision model of Educative, Supportive, and Administrative Cycle (ESA-C) is made to increase the positive value of supervision. The model is synthesized from Kadushin’s and Proctor’ supervision models integrated with Peplau’s interpersonal relationship theory and Watson’s carative factors. The research aims to test the effectiveness of ESA-C clinical supervision model in improving nurse performance using the quasi-experimental design of two group pre-post-tests. Two hospitals were randomly selected from the five public hospitals as the research location. The sample consisted of 90 nurses and 270 patients, taken randomly and purposively, respectively. The results indicate that the ESA-C clinical supervision model was able to significantly improve the nurses’ performance (p-value < 0.05) in the dimensions of task performance: technical skills improved by 2%, patient education 9%, emotional support to patients 14%; and contextual performance: assistance to patients and families improved by 21%. It is recommended that the model be used in nursing care, especially in hospitals, in an attempt of improving nurse performance in providing nursing care to patients.